Determinants of female employment status in Pakistan: A case of Sahiwal District - Ruqia Shaheen; Ghulam Shabir; Muhammad Zahir Faridi; Fouzia Yasmin (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
The leading intention of this research work is to determine the various factors that determine female employment status (engagement of females in different employment activities). The data have been collected through field survey which consists of 402 females. We have used binominal and multinominal logistic regression model for the analysis. We have concluded that age, educational attainment, marital status and presence of children above 10 years have a positive impact on female employment. Presence of children below 10 years, assets, major disease and household size negatively and significantly related to female employment. Total working in family and number of dependents positively affect female decision as an active earner while have a negative effect on self-employment and underemployment. The study suggests that huge investment should be made for the provision of educational facilities. To improve the health condition of workers health facilities should be provided to everyone.
Keywords: 330; employment status; age; education; marital status; household size; logistic regression model; Pakistan